Method for producing super absorbent polymer

JP2025021045APending Publication Date: 2025-02-13NIPPON SHOKUBAI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023124741
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、使用済み吸収性物品に含まれる吸水性樹脂、吸水性樹脂製造工程中の廃棄吸水性樹脂などの本来廃棄すべき吸水性樹脂を使用して、吸水性能(特に加圧下吸水倍率)を改善した吸水性樹脂を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021045000001
    Figure 2025021045000001
Patent Text Reader

Abstract

To provide a technique that improves water absorption performance (particularly absorption ratio under pressure) by using super absorbent polymers originally meant to be discarded, such as super absorbent polymers contained in absorbent articles, as well as waste super absorbent polymers during the super absorbent polymer manufacturing processes.SOLUTION: A method for producing super absorbent polymers involves producing a super absorbent polymer by using, as part of the starting material, a super absorbent polymer decomposition product formed by decomposing the recovered super absorbent polymer. The method includes a gel crushing step for mixing a hydrogel-like crosslinked polymer formed by polymerizing an unsaturated monomer, the super absorbent polymer decomposition product, and a crosslinker.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a water-absorbent resin. In particular, the present invention relates to a method for producing a water-absorbent resin, in which a decomposition product of the water-absorbent resin obtained by decomposing used absorbent articles or waste materials during a water-absorbent resin production process is used as a part of a raw material during the production of the water-absorbent resin. [Background technology]

[0002] Super absorbent polymers (SAP) are water-swellable, water-insoluble polymer gelling agents that are used in a variety of absorbent products, including disposable diapers, sanitary napkins, adult incontinence products (incontinence pads), hygiene materials (sanitary products) such as pet sheets, soil water retention agents for agricultural and horticultural use, and industrial water-stopping agents.

[0003] Among these, the main applications of water-absorbent resins are sanitary materials such as disposable diapers and sanitary napkins. After being used for a short period of time (at most about one day), these sanitary materials are discarded in large quantities as used absorbent articles and incinerated.

[0004] In recent years, from the viewpoint of environmental protection, attempts have been made to recycle such used absorbent articles. For example, sanitary materials contain raw materials such as pulp, nonwoven fabric, adhesives, etc. in addition to the above-mentioned water-absorbent resin, and material recycling has been attempted in which these raw materials are separated from used sanitary materials and reused. Furthermore, a technology has been developed to recycle decomposition products of water-absorbent resin obtained from sanitary products for the manufacture of water-absorbent resin (Patent Documents 1-2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2020 / 213298 [Patent Document 2] International Publication No. 2022 / 080342 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the water-absorbing performance (particularly, water absorption capacity under pressure) of the water-absorbing resin obtained by recycling the decomposition product of the water-absorbing resin by the above-mentioned technique is not sufficient, and further improvement is required.

[0007] Therefore, the present invention has been made in consideration of the above circumstances, and aims to provide a technique for improving water absorption performance (particularly, water absorption capacity under pressure) when producing a water absorbent resin using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process. [Means for solving the problem]

[0008] The present inventors have conducted intensive research to solve the above problems. As a result, they have found that the above problems can be solved by mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, a decomposition product of the water-absorbent resin, and a crosslinking agent in a gel crushing step when producing a water-absorbent resin using a decomposition product of the water-absorbent resin obtained by decomposing a recovered water-absorbent resin such as a water-absorbent resin contained in a used absorbent article or a waste water-absorbent resin during a water-absorbent resin production process as a part of a raw material, and thus completing the present invention.

[0009] That is, the above-mentioned object can be achieved by a method for producing a water-absorbent resin, which comprises producing a water-absorbent resin by using a decomposed product of the water-absorbent resin obtained by decomposing a recovered water-absorbent resin as a part of a raw material, and mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, the decomposed product of the water-absorbent resin, and a crosslinking agent in a gel crushing step. Effect of the Invention

[0010] According to the present invention, a water absorbent resin having improved water absorption performance (particularly, water absorption capacity under pressure) can be produced by using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] One aspect of the present invention relates to a method for producing a water-absorbent resin, which comprises producing a water-absorbent resin using a water-absorbent resin decomposition product obtained by decomposing a recovered water-absorbent resin as part of a raw material, and mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, the water-absorbent resin decomposition product, and a crosslinking agent in a gel crushing step. With this configuration, even when a water-absorbent resin is produced using a water-absorbent resin that should be discarded, such as a water-absorbent resin contained in a used absorbent article or a water-absorbent resin discarded during a water-absorbent resin production step, as part of the raw material, the water-absorbent resin can be produced with improved water-absorption performance (particularly, water absorption capacity under pressure).

[0012] In this specification, the "decomposition product of the water-absorbent resin" is also simply referred to as the "decomposition product" or the "decomposition product according to the present invention". The "water-absorbent resin produced by the method of the present invention" is also simply referred to as the "water-absorbent resin" or the "water-absorbent resin according to the present invention".

[0013] The water absorbent resin obtained by adding a water absorbent resin decomposition product as in the technology of Patent Documents 1 and 2 has a problem that the water absorption properties, particularly the water absorption capacity under pressure, are lower than that of a normal water absorbent resin to which no water absorbent resin decomposition product is added. When the present inventors conducted research on the above problem, they found that the water absorbent resin using a water absorbent resin decomposition product as a part of the raw material tends to have a large amount of water soluble content (soluble polymer amount), and they presumed that this is one of the causes of the decrease in the water absorption properties, particularly the water absorption capacity under pressure, of the produced water absorbent resin. The present inventors further conducted intensive research on the reduction of the water soluble content. As a result, they presumed that the presence of the absorbent resin decomposition product independent of the water absorbent resin (in a free state) is the cause of the increase in the water soluble content, and thus the decrease in the water absorption properties (particularly the water absorption capacity under pressure) of the final product water absorbent resin. Therefore, from the viewpoint of reducing the water-soluble content, the inventors have conducted intensive research into means for improving the water absorption properties (particularly, the water absorption capacity under pressure), and have found that by mixing the water-absorbent resin decomposition product with the hydrous gel-like crosslinked polymer in the presence of a crosslinking agent, the absorbent resin decomposition product is easily chemically incorporated into the crosslinked polymer, and the decrease in the water absorption properties, particularly the water absorption capacity under pressure, can be suppressed. In particular, in the hydrous gel-like crosslinked polymer, since the polymer is in a hydrous state, the crosslinking agent easily penetrates into the inside of the gel, and since the polymer molecular chains in the gel are in a spread state, the crosslinking reaction is easily carried out efficiently.

[0014] It should be noted that the above mechanism is merely speculation and does not limit the technical scope of the present invention.

[0015] Preferred embodiments of the present invention will be described below. Note that the present invention is not limited to the following embodiments, and can be modified in various ways within the scope of the claims. In addition, the embodiments described in this specification can be combined in any manner to form other embodiments.

[0016] As used herein, the term "(meth)acrylic" includes both acrylic and methacrylic. Thus, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. As used herein, "acid (salt)" means "acid and / or its salt."

[0017] [1] Definitions of terms [1-1] Water-absorbing resin The "water-absorbent resin" produced by the method of the present invention is a water-swellable, water-insoluble polymer gelling agent, and refers to a conventional water-absorbent resin having a water-absorption capacity of 10 to 1000 times, although it is not particularly limited thereto. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed preferably satisfies the physical property of CRC of 5 g / g or more as "water-swellability". The definition of CRC will be described later.

[0018] The water-absorbing resin may be a polymer derived from a carboxyl group-containing unsaturated monomer. The water-absorbing resin may include a polymer having a partially neutralized carboxyl group. Specific examples of the water-absorbing resin include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.

[0019] In this specification, the water-absorbing resin is not limited to an embodiment in which the total amount (100 mass %) is the water-absorbing resin alone, but may be a water-absorbing resin composition containing additives and the like.

[0020] [1-2] Recycled water-absorbent resin The term "recovered water-absorbent resin" refers to water-absorbent resin that should be discarded. Specifically, the term includes water-absorbent resin contained in used absorbent articles (for example, water-absorbent resin that has absorbed body fluids such as urine and blood in used absorbent articles) and water-absorbent resin discarded during the water-absorbent resin manufacturing process (for example, fine powder or non-standard water-absorbent resin generated during the water-absorbent resin manufacturing process).

[0021] Among these, it is preferable to use a water-absorbent resin recovered (removed and collected) from used absorbent articles from the viewpoint of environmental protection, etc. That is, in one embodiment of the present invention, the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article.

[0022] Here, "used absorbent articles" refer to sanitary materials that have been used by consumers and have absorbed bodily fluids such as urine and blood. Examples of sanitary materials include paper diapers, sanitary napkins, and adult incontinence products (incontinence pads). Products similar to sanitary materials include pet sheets and pet diapers, and in the present invention, these animal urine treatment products are also included in the sanitary materials.

[0023] The recovered water-absorbent resin is not limited to an embodiment in which the total amount (100% by mass) is the water-absorbent resin alone, and may be a water-absorbent resin composition containing a fibrous substance, a nonwoven fabric, an adhesive, an additive, etc. In addition, when the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article, the recovered water-absorbent resin may be in a state of a hydrous gel in which water such as urine water has been taken in. Therefore, the water-absorbent resin may contain a water-absorbent resin in a state of a hydrous gel.

[0024] The mass of the water-absorbing resin and the recovered water-absorbing resin is a value converted into solid content unless otherwise specified. For example, when the mass of the water-absorbing resin contained in the used paper diaper is unknown, the mass of the water-absorbing resin contained in the unused paper diaper and the general value of the water absorption ratio of the water-absorbing resin in the used paper diaper are used for calculation, or the content of the water-absorbing resin (solid content equivalent value) relative to the total mass of the used paper diaper is assumed to be 3% by mass or more and 9% by mass or less, and the mass of the water-absorbing resin is measured. Although the actual content of the water-absorbing resin may vary greatly depending on the usage state of the used paper diaper, a person skilled in the art can adjust the decomposition conditions appropriately while checking the actual decomposition state.

[0025] In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (which is the raw material of the decomposition product) is 20 g / g or more, 25 g / g or more, 27 g / g or more, or 30 g / g or more. In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (which is the raw material of the decomposition product) is 70 g / g or less, 50 g / g or less, or 45 g / g or less. The definition of CRC is as described in [1-5-1] below.

[0026] In one embodiment of the present invention, the AAP (0.3 psi) of the recovered water absorbent resin (the raw material of the decomposition product) is 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, or 25 g / g or more. In one embodiment of the present invention, the AAP (0.3 psi) of the water absorbent resin (the raw material of the decomposition product) is 50 g / g or less, 45 g / g or less, 40 g / g or less, 35 g / g or less, or 30 g / g or less. The definition of AAP is as described in [1-5-2] below.

[0027] [1-3] Absorbent articles An "absorbent article" is an article used for absorbing water. More specifically, an "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbent resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbent resin with a fibrous material, or by sandwiching a water-absorbent resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or the like. Examples of the fibrous material include hydrophilic fibers such as ground wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like.

[0028] The term "absorbent article" includes both unused absorbent articles and used absorbent articles. Here, "used absorbent articles" particularly include used sanitary materials that have absorbed body fluids (absorbed liquids) such as urine and blood. Examples of the sanitary materials include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.

[0029] [1-4] Decomposition product The "decomposition product" is a product obtained by decomposing a water-swellable (i.e., insoluble in water) recovered water-absorbent resin, and can be solubilized in water. The decomposition product may be a product that is entirely solubilized in water, or a product that is partially solubilized. If the product appears dissolved in water with no residual residue visible in the water (if the interface between the water-absorbent resin and water cannot be visually recognized in the water), it is deemed to be solubilized in water. If some undissolved swollen matter remains but is reduced compared to before the solubilization treatment, it is deemed to be partially solubilized and a decomposition product is generated. Therefore, even if some undissolved swollen matter remains in the aqueous decomposition product solution after decomposition (solubilization), it is referred to as an aqueous decomposition product solution (or a dispersion of decomposition product). The obtained decomposition product may be used as it is in the form of an aqueous solution. Alternatively, the obtained decomposition product may be used in a solid state after drying to make it into a solid.

[0030] In one embodiment of the present invention, the mass average molecular weight of the decomposition product is 30,000 or more and 1,000,000 or less, or 40,000 or more and 800,000 or less. If the mass average molecular weight is within the above range, the amount of water-soluble content of the water-absorbent resin produced by using the decomposition product as a part of the raw material can be further reduced, and the water absorption properties can be further improved. In addition, the viscosity of the decomposition product solution (e.g., aqueous solution) can be appropriately controlled, so that the handling property is excellent. The definition of the mass average molecular weight is as described in [1-5-4] below.

[0031] [1-5] EDANA and WSP "EDANA" is an abbreviation for European Disposables and Nonwovens Associations, and "WSP" is an abbreviation for World Strategic Partners. EDANA and WSP are European and American standards (almost global standards) for measuring the physical properties of water-absorbent resins. In the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original EDANA WSP (revised in 2010 / publicly known document).

[0032] "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."

[0033] [1-5-1] CRC In this specification, the absorbency without load (CRC) is a value measured according to the following method.

[0034] (Measurement of Absorption Capacity under No Load (CRC)) "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity," and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure in a 0.90 mass % sodium chloride aqueous solution.

[0035] 0.200 g of water-absorbent resin is evenly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22), heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag is pulled out and drained for 3 minutes using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122) at a centrifugal force (250 G) described in edana ABSORBENCY II 441.1-99, and the mass W1 (g) of the bag is measured. In addition, the same operation is performed without using the water-absorbent resin, and the mass W0 (g) at that time is measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) is calculated according to the following formula (1).

[0036] Formula (1): CRC(g / g)=(W1-W0) / (mass of water-absorbent resin)-1 [1-5-2] AAP0.3 (absorption rate under pressure) The "AAP" of the water absorbent resin of the present invention is an abbreviation for "Absorption Against Pressure" and indicates the absorbency against pressure (unit: g / g) for a 0.90 mass% sodium chloride aqueous solution. In this specification, unless otherwise specified, "AAP0.3", "absorption against pressure", and "AAP" are treated as synonyms.

[0037] AAP0.3 is measured in accordance with NWSP 242.0.R2(15) except that the pressure condition is changed from 0.7 psi to 0.3 psi. Specifically, a large excess of 0.9% by mass sodium chloride aqueous solution is used, and 0.9 g of the water-absorbent resin is subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.3 psi (0.02 psi), the AAP (absorbency under pressure) is measured. "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."

[0038] [1-5-3] Solids concentration of decomposition products The solid content concentration of the decomposition product was measured by the following method. That is, the decomposition product with mass Wa (g) was placed on an aluminum plate with mass Wb (g) and dried in a hot air circulating oven at 180°C for 3 hours, and then the total mass Wc (g) of the decomposition product and the aluminum plate was measured. The solid content concentration of the decomposition product was calculated according to the following formula (2).

[0039] Formula (2): Solid concentration of decomposition product (mass%) = {(Wc-Wb) / Wa} x 100 [1-5-4] Molecular weight of decomposition products (Preparation of measurement samples) The sample is dissolved in the following solvent to obtain a solution with a concentration of 0.1% by mass. The resulting solution is then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to obtain the measurement sample. Solvent: Aqueous solution (pH 6.35 to 6.38) containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM disodium hydrogen phosphate dodecahydrate, and 400 ppm sodium azide. Using this measurement sample, perform GPC measurement under the following measurement conditions.

[0040] (GPC measurement conditions) The sample was subjected to GPC measurement using Viscotec TDAmax manufactured by Malvern Instruments. The measurement device is equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector and a capillary viscometer. The measurement device and measurement conditions are as follows. Pump, autosampler: Viscotec GPCmax (Malvern) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: Two OHpak SB-806MHQ (Showa Denko K.K.) columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μL.

[0041] The water used in GPC measurement should be pure water from which impurities have been thoroughly removed. In addition, GPC measurement should be performed with a sufficient amount of solvent flowing through the measurement device, with the baseline of the detection value stable, and in particular, with no noise peaks in the light scattering detector.

[0042] The measurement device is calibrated using polyoxyethylene glycol [mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33] as a standard sample. The measurement is performed with the differential refractive index (dn / dc) of the decomposition product to be measured set to 0.12 and the solvent refractive index set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity are performed using Viscotek OmniSEC4.7.0 (registered trademark) software.

[0043] After the measurement, the data obtained from the refractive index (RI) and light scattering intensity (angle: 7°) (LALS), as well as the viscometer (DP) are used to calculate the mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the decomposition products.

[0044] [1-5-5] Decomposition rate of decomposition products 200.0 g of 0.90% by weight sodium chloride solution was weighed out into a 250 ml glass container with a 35 mm long rotor, and then 1.00 g of the decomposition product was added to the aqueous solution and the container was covered with plastic wrap. The mixture was then stirred at room temperature for 16 hours (500 rpm) using a stirrer. The above operation allowed the extraction of water-soluble components in the decomposition product.

[0045] After stirring, the aqueous solution, that is, the extract, is filtered using a sheet of filter paper (manufactured by ADVANTEC Toyo Co., Ltd.; product name: JIS P3801, No. 2 / thickness 0.26 mm, retention particle size 5 μm), and 50.0 g of the resulting filtrate is used as the measurement liquid.

[0046] Next, the measurement solution is titrated with a 0.1N-NaOH aqueous solution until the pH becomes 10, and then titrated with a 0.1N-HCl aqueous solution until the pH becomes 2.7. The titration amounts at this time are calculated as [NaOH] ml and [HCl] ml, respectively.

[0047] In addition, the same procedure is carried out using 200.0 g of 0.90% by mass sodium chloride aqueous solution without adding any decomposition product, and the blank titer ([b1NaOH] ml and [b1HCl] ml) is calculated.

[0048] The decomposition rate is calculated from the titration amount and the average molecular weight of the monomer according to the following formula (3).

[0049] Formula (3): Decomposition rate (mass%) = 0.1 × average molecular weight of monomer × 200 × 100 × ([HCl]-[b1HCl]) / 1000 / 1.0 / 50.0 / (solid concentration of decomposition product / 100) When the monomer average molecular weight is unknown, the monomer average molecular weight is calculated using the neutralization rate calculated by the following formula (4).

[0050] Formula (4): Neutralization rate (mol%) = {1-([NaOH]-[b1NaOH]) / ([HCl]-[b1HCl])} x 100 [2] Method for producing a water-absorbing resin according to one embodiment of the first aspect In one embodiment of the present invention, the method for producing a water-absorbent resin of the present invention comprises producing a water-absorbent resin by using a decomposition product of the water-absorbent resin obtained by decomposing a recovered water-absorbent resin as a part of a raw material, and mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, the decomposition product of the water-absorbent resin, and a crosslinking agent in a gel crushing step.

[0051] [2-1] A process for preparing a water-absorbent resin decomposition product The recovered water-absorbent resin is decomposed to prepare a water-absorbent resin decomposition product. Here, the water-absorbent resin decomposition product may be produced by decomposing the recovered water-absorbent resin, may be a product obtained by commissioning another company to decompose the recovered water-absorbent resin, or may be a purchased water-absorbent resin decomposition product.

[0052] The method for producing the water absorbent resin decomposition product (decomposition product) is not particularly limited, and a known method can be used. For example, a technique for solubilizing the water absorbent resin by heating a mixture of water absorbent resin and pulp in the presence of an oxidizing agent such as hydrogen peroxide or persulfate (e.g., JP-A-4-317785, JP-A-6-313008, JP-A-2003-321574), a technique for solubilizing the water absorbent resin using ascorbic acid as a reducing agent under conditions of pH 4 to 7.5 (e.g., JP-A-05-247221), a technique for solubilizing the water absorbent resin using a reducing agent and a transition metal ion (e.g., JP-A-2019-131789), and a technique for solubilizing the water absorbent resin by heating in the presence of an oxidizing water-soluble salt (e.g., WO2021 / 042113). As a technique for decomposing a superabsorbent resin and solubilizing it in water, for example, a technique for solubilizing a water-absorbent resin using ozone water (e.g., JP 2014-217835 A, JP 2017-100133 A), a technique for solubilizing a water-absorbent resin using a combination of an oxidizing agent and a transition metal ion such as an iron ion or a copper ion (e.g., JP 11-172039 A), a technique for oxidation treatment with hypochlorous acid (salt), hydrogen peroxide, persulfuric acid, chlorine or a water-soluble oxidizing and reducing agent (e.g., JP 2013-150977 A), and a technique for solubilizing a water-absorbent resin using an alkaline compound (e.g., JP 2020-49398 A) can be used.

[0053] An embodiment for producing a decomposition product will be described below, but the present invention is not limited to the following.

[0054] The recovered water absorbent resin and the decomposing agent are mixed. At this time, it is preferable to add water. Here, the water is not particularly limited as long as it is clean, and examples thereof include tap water, industrial water, ion-exchanged water, and pure water. The mixing ratio of water and the recovered water absorbent resin (solid content) is not particularly limited. As described later, in a preferred embodiment of the present application, the solid content concentration of the water absorbent resin and the solid content concentration of the decomposition product may be considered, so the mixing amount of water is appropriately set according to the embodiment. The mixing amount of water is, for example, 0.1 parts by mass or more and 1900 parts by mass or less, 0.5 parts by mass or more and 1500 parts by mass or less, or 1 part by mass or more and 1000 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin (solid content). If the mixing amount of water is the lower limit or more, the mixing of the recovered water absorbent resin and the decomposing agent is performed uniformly and sufficient decomposition can be performed. In addition, if the mixing amount of water is the upper limit or less, the resulting decomposition product is obtained at a sufficient concentration, so that it can be used as it is or simply concentrated in the subsequent manufacturing process. When the recovered water-absorbent resin is in a state of a hydrous gel, the water absorbed in the water-absorbent resin may be used as it is.

[0055] When preparing (manufacturing) a decomposition product from recovered water-absorbent resin contained in used absorbent articles, it is preferable to wash the used absorbent articles and recovered water-absorbent resin in advance to remove human waste and the like, and then perform the decomposition operation.

[0056] The decomposing agent is not particularly limited as long as it can decompose the recovered water absorbent resin and solubilize it in water, and may be any decomposing agent. Examples of the decomposing agent include an oxidizing agent, ozone water, a combination (mixture) of an oxidizing agent and a reducing agent, a combination (mixture) of an oxidizing agent and a transition metal ion such as iron ion or copper ion, a combination (mixture) of a reducing agent and a transition metal ion, and an alkali compound. When a decomposing agent (e.g., an oxidizing agent, an iron ion, an alkali compound, etc.) is contained in the recovered water absorbent resin, these decomposing agents may be used as they are.

[0057] An oxidizing agent may be used as the decomposition agent. The oxidizing agent is a compound having oxidizing properties and generates radicals by heating. Radicals are also generated by using an oxidizing agent in combination with a reducing agent and / or a compound that generates transition metal ions. Examples of the oxidizing agent include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. The oxidizing agent may be used alone or in combination of two or more. Of these, hydrogen peroxide is preferably used. In this embodiment, the amount of the oxidizing agent is preferably 0.1 parts by mass or more and 50 parts by mass or less, more preferably 0.3 parts by mass or more and 30 parts by mass or less, and even more preferably 0.5 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. When the amount of the oxidizing agent is within the above range, the recovered water absorbent resin can be efficiently decomposed, and coloration of the resulting decomposition product can be sufficiently prevented.

[0058] A reducing agent may be used as the decomposing agent. The reducing agent is a compound having reducing properties, and generates radicals when used in combination with the above-mentioned oxidizing agent or the below-mentioned compound that generates transition metal ions. Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salt) or its derivatives (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphoric acid esters, and sulfate esters. The reducing agent may be used alone or in combination of two or more kinds. Among these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used. In this embodiment, the amount of the reducing agent is preferably 0.01 parts by mass or more and 50 parts by mass or less, more preferably 0.05 parts by mass or more and 25 parts by mass or less, and even more preferably 0.1 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. With this amount of the reducing agent, the recovered water absorbent resin can be efficiently decomposed, and coloring of the resulting decomposition product can be sufficiently prevented.

[0059] A transition metal ion may be used as the decomposition agent. The transition metal ion generates radicals by the Fenton reaction when used in combination with the above-mentioned oxidizing agent. Also, the transition metal ion generates radicals when used in combination with the above-mentioned reducing agent. Examples of the transition metal ion include Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ The transition metal ions may be used alone or in combination of two or more. Among these, iron ion (Fe 2+ ), copper ions (Cu 2+ ) is preferred, and iron ions (Fe 2+) is more preferable. Examples of the compound that generates the transition metal ions as described above include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, sulfates and hydrates thereof, such as ferrous sulfate, and the like. The compounds may be used alone or in combination of two or more. In this embodiment, the amount of transition metal ions is 1×10 to 100 parts by mass of the recovered water absorbent resin. -6 It is preferably from 1 part by mass to 1 part by mass, and more preferably from 1×10 -5 The amount of the transition metal ion is preferably from 0.001 to 0.1 parts by mass, more preferably from 0.02 to 0.5 parts by mass, and even more preferably from 0.001 to 0.1 parts by mass. The amount of the transition metal ion is such that the recovered water absorbent resin can be efficiently decomposed and coloration of the resulting decomposition product can be sufficiently prevented.

[0060] An alkaline compound may be used as the decomposing agent. The alkaline compound is a compound that solubilizes the crosslinked portion of the water-absorbent resin by alkaline hydrolysis. Examples of such alkaline compounds include hydroxides of alkali metals such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; hydroxides of alkaline earth metals such as magnesium hydroxide and calcium hydroxide; ammonia; and amine compounds such as aliphatic amines, alicyclic amines, and aromatic amines. The alkaline compounds may be used alone or in combination of two or more kinds. Among these, hydroxides of alkali metals and hydroxides of alkaline earth metals are preferred.

[0061] The decomposition conditions are not particularly limited, but it is preferable to carry out the decomposition under appropriate pH conditions. Specifically, it is preferable to adjust the pH of the mixture containing the recovered water absorbent resin, water, and the decomposition agent to a range of 6.5 to 8.5 (more preferably 6.5 to 8.3, particularly preferably 6.5 to 8.0). If the pH is within the above range, the recovered water absorbent resin can be efficiently decomposed, and coloring of the resulting decomposition product can be sufficiently prevented. The pH of the mixture may be adjusted within the range for a certain period of time that allows the decomposition of the recovered water absorbent resin to proceed sufficiently. It is preferable to adjust the pH to fall within the above pH range from the start of decomposition to the end of decomposition. The pH of the mixture can be adjusted by adding a pH adjuster such as an acid or a base as necessary. Examples of acids to be used include, but are not limited to, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid and citric acid. Examples of bases that can be used include, but are not limited to, sodium hydroxide, sodium carbonate, potassium hydroxide hydroxide, and magnesium hydroxide.

[0062] The temperature at which the recovered water absorbent resin is decomposed is preferably 50°C or higher and 200°C or lower, more preferably 65°C or higher and 200°C or lower, and even more preferably 80°C or higher and 190°C or lower. At the above temperature, a sufficient amount of radicals is generated from the decomposing agent, and the decomposition product can be obtained in a short time. The decomposition temperature can also be adjusted to adjust the decomposition rate and molecular weight of the decomposition product of the recovered water absorbent resin. As a method for adjusting the decomposition temperature, the recovered water absorbent resin, the decomposing agent, and water may be mixed at room temperature (e.g., 20°C or higher and 25°C or lower), and then the temperature of the mixture may be adjusted to a predetermined value while stirring if necessary. Alternatively, the recovered water absorbent resin, the decomposing agent, and water may be mixed at room temperature (e.g., 20°C or higher and 25°C or lower), and then the recovered water absorbent resin, the decomposing agent, and water may be introduced into a container whose temperature has been adjusted to a predetermined temperature by a known means such as an oil bath, and then stirred.

[0063] After the decomposition reaction is completed, the decomposition agent may be removed by, for example, adding a basic substance such as sodium carbonate and stirring the mixture for a certain period of time under alkaline conditions when the decomposition agent is an oxidizing agent such as hydrogen peroxide.

[0064] In order to adjust the solid content concentration of the decomposition product, an additional drying treatment may be carried out.

[0065] The decomposition operation produces a decomposition product (water-absorbent resin decomposition product). The decomposition product may be in a liquid state or a powder state.

[0066] The decomposition rate of the decomposition product is preferably 70% or more (upper limit 100%), more preferably 75% or more, further 80% or more, and even more preferably 90% or more. By using a decomposition product with such a high decomposition rate, the effects of the present invention are further enhanced. The decomposition rate may be adjusted to be within the above range. The method for adjusting to be within the above range is not particularly limited, and specific examples include increasing the amount of decomposition agent used, extending the decomposition time, increasing the decomposition temperature, decreasing the viscosity of the decomposition system (aqueous solution containing a water-absorbent resin and a decomposition agent), and using a kneader with excellent stirring properties.

[0067] [2-2] A process for producing a water-absorbent resin using a decomposition product of the water-absorbent resin as part of the raw material In a preferred embodiment, the method for producing a water-absorbent resin of the present invention includes a polymerization step of polymerizing an unsaturated monomer-containing aqueous solution to obtain a hydrogel-like crosslinked polymer, a gel crushing step of gel-crushing the hydrogel-like crosslinked polymer, and a drying step of drying the gel-like crushed product. Preferably, this production method further includes a surface crosslinking step. More preferably, this production method includes at least one of a cooling step, a crushing step of the dried product, a classification step, a surface crosslinking step, or a sizing step after surface crosslinking. In addition, the method may include a preparation step of an unsaturated monomer-containing aqueous solution (hereinafter also simply referred to as a monomer aqueous solution), an addition step of various additives, a fine powder removal step, a fine powder recycling step (fine powder recovery step), or a filling step. Furthermore, various known steps may be included depending on the purpose. In addition, the method for producing a water-absorbent resin of the present invention may include a step of preparing the water-absorbent resin decomposition product.

[0068] Each step will be described below.

[0069] [2-2-1] Monomer aqueous solution preparation process This step is a step of preparing an aqueous solution containing an unsaturated monomer, preferably a carboxyl group-containing unsaturated monomer, particularly acrylic acid (salt), as a main component (hereinafter referred to as "aqueous monomer solution"). Although a monomer slurry liquid can also be used within a range in which the water absorption performance of the resulting water absorbent resin is not reduced, for the sake of convenience, the aqueous monomer solution will be described in this section.

[0070] The "main component" means that the amount (content) of the unsaturated monomer (particularly, a carboxyl group-containing unsaturated monomer, an acrylic acid (salt)) used is usually 50 mol % or more, preferably 70 mol % or more, more preferably 90 mol % or more (upper limit: 100 mol %) relative to the monomer (excluding an internal crosslinking agent; the same applies below) to be subjected to a polymerization reaction of the water absorbent resin.

[0071] As the solvent for the aqueous monomer solution, water or a mixture of water and a water-soluble organic solvent (e.g., alcohol, etc.) is preferably used, and water is even more preferred. In the case of a mixture of water and a water-soluble organic solvent, the content of the water-soluble organic solvent (e.g., alcohol, etc.) is preferably 30% by mass or less, and more preferably 5% by mass or less, when the total mass of the solvent is taken as 100% by mass.

[0072] In the following, a case where the monomer is acrylic acid (salt) will be described, but the present invention is not limited to the following.

[0073] (acrylic acid) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the obtained water absorbent resin, acrylic acid and / or a salt thereof (hereinafter, referred to as "acrylic acid (salt)") is used as a monomer constituting the water absorbent resin.

[0074] The "acrylic acid" may be a known acrylic acid, and may contain a polymerization inhibitor, preferably 200 ppm or less, more preferably 10 ppm or more and 160 ppm or less, and even more preferably 20 ppm or more and 100 ppm or less, from the viewpoint of the polymerizability of acrylic acid and the color tone of the water-absorbing resin. The polymerization inhibitor is preferably a methoxyphenol, more preferably p-methoxyphenol. In addition, as for impurities in acrylic acid, the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 are also applicable to one embodiment of the present invention.

[0075] The "acrylate" is obtained by neutralizing the acrylic acid with the following basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water-absorbent resin manufacturing plant.

[0076] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, such as a commercially available aqueous sodium hydroxide solution.

[0077] Specific examples of the basic compound include carbonates and / or hydrogen carbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, and the like. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, it is desirable to use a strong basic compound. That is, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred, and sodium hydroxide is more preferred. That is, the salt of acrylic acid is preferably at least one selected from alkali metal salts, ammonium salts, and amine salts of acrylic acid, more preferably an alkali metal salt of acrylic acid, even more preferably at least one selected from sodium salts, lithium salts, and potassium salts of acrylic acid, and particularly preferably a sodium salt of acrylic acid.

[0078] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization of acrylic acid (before polymerization) or neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. When the decomposition product is used as at least a part of the raw material in the production of a water-absorbent resin, if the decomposition product contains a basic compound, this basic compound neutralizes the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, the neutralization rate of the water-absorbent resin as the final product may be adjusted to a predetermined range by adding this basic compound. Regarding the conditions such as the apparatus for performing neutralization, the neutralization temperature, and the residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 may also be applied to the present invention. The neutralization in one embodiment of the present invention may be performed by adding a basic compound to the aqueous monomer solution in multiple stages. In addition, the neutralization in one embodiment of the present invention may be performed in a continuous or batch manner.

[0079] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, even more preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. With such a neutralization rate, a water-absorbing resin with high water absorption properties (particularly water absorption capacity under pressure) can be obtained. For example, a neutralization rate of 75 mol% means a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. This may also be called a partially neutralized product of acrylic acid.

[0080] The neutralization rate is the same in the case of post-neutralization. The neutralization rate is also applied to the neutralization rate of the water-absorbent resin as a final product. The present invention is characterized in that the recycled water-absorbent resin is used as a part of the raw material in the production of the water-absorbent resin. When the recycled water-absorbent resin contains the basic compound, the neutralization of the acrylic acid (before polymerization) and / or the post-neutralization of the hydrogel-like crosslinked polymer is appropriately adjusted so that the neutralization rate of the water-absorbent resin as a final product, including the basic compound, falls within a predetermined range.

[0081] (Other monomers) In one embodiment of the present invention, the term "other monomer" refers to a monomer other than the acrylic acid (salt), and the water-absorbing resin can be produced by using the other monomer together with the acrylic acid (salt).

[0082] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, the compounds described in U.S. Patent Application Publication No. 2005 / 0215734 (excluding acrylic acid) are also applicable to one embodiment of the present invention.

[0083] (Polymerization initiator) A polymerization initiator can be used in the preparation of the monomer aqueous solution, if necessary. The polymerization initiator is not particularly limited, since it is appropriately selected depending on the polymerization form, etc. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. In addition, from the viewpoint of the handling of the polymerization initiator, the physical properties of the water-absorbing resin, etc., preferably a peroxide or an azo compound, more preferably a peroxide, even more preferably a persulfate such as sodium persulfate, potassium persulfate, or ammonium persulfate, and particularly preferably sodium persulfate is used.

[0084] The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.005 mol% or more and 0.5 mol% or less, and even more preferably 0.01 mol% or more and 0.3 mol% or less, based on the monomers used in the polymerization reaction of the water absorbent resin. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomers. The mol% based on the monomers refers to the percentage of the number of moles of the polymerization initiator or the reducing agent based on the total number of moles of the monomers (excluding the internal crosslinking agent) contained in the aqueous monomer solution.

[0085] If necessary, the photodecomposition type polymerization initiator may be used in combination with other polymerization initiators such as a photodecomposition type polymerization initiator. Specific examples of the photodecomposition type polymerization initiator include benzoin derivatives, benzyl derivatives, acetophenone derivatives, and benzophenone derivatives.

[0086] Instead of the polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or these active energy rays may be used in combination with the polymerization initiator.

[0087] (Internal crosslinking agent) An internal crosslinking agent is used in the preparation of the monomer aqueous solution. The crosslinked structure may be composed of a monomer and an internal crosslinking agent. As the internal crosslinking agent, the compounds described in U.S. Pat. No. 6,241,928 are also applied to one embodiment of the present invention. Among these, one or more compounds are selected in consideration of reactivity.

[0088] From the viewpoint of the water absorption performance of the obtained water absorbent resin, a compound having two or more polymerizable unsaturated groups in one molecule is preferably used as the internal crosslinking agent. More preferably, a compound having thermal decomposition properties, and even more preferably, a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit, is used as the internal crosslinking agent.

[0089] The polymerizable unsaturated group is preferably an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.

[0090] Examples of such internal crosslinking agents include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane di(meth)acrylate, glycerin tri(meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkane, etc. These internal crosslinking agents may be used alone or in combination of two or more.

[0091] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more and 5 mol% or less, more preferably 0.001 mol% or more and 1.5 mol% or less, and particularly preferably 0.01 mol% or more and less than 1.0 mol% with respect to the monomer (excluding the internal crosslinking agent). By setting the amount used within the above range, a desired water absorbent resin can be obtained. With such an amount used, it is possible to suppress a decrease in gel strength and an increase in water-soluble matter, and to achieve excellent water absorption properties. The mol% with respect to the total monomer is the percentage of the number of moles of the internal crosslinking agent with respect to the total number of moles of the monomer (excluding the internal crosslinking agent) contained in the monomer aqueous solution.

[0092] In one embodiment of the present invention, a method is preferably applied in which a predetermined amount of an internal crosslinking agent is added to an aqueous monomer solution in advance, and a crosslinking reaction is carried out simultaneously with polymerization. On the other hand, other than the above method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization, a radical crosslinking method using a radical polymerization initiator, a radiation crosslinking method using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.

[0093] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances may be added during preparation of the aqueous monomer solution.

[0094] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in amounts of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass); foaming agents such as carbonates and azo compounds, surfactants, chelating agents, chain transfer agents, etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass); and the like.

[0095] In addition, the following substances (hereinafter referred to as "other substances") may be added to the aqueous monomer solution. Specific examples of other substances include chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites; foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles; chelating agents such as metal salts of ethylenediaminetetraacetic acid and metal salts of diethylenetriaminepentaacetic acid; thickeners such as polyacrylic acid (salts) and crosslinked products thereof, starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol. The other substances may be used alone or in combination of two or more.

[0096] The amount of other substances used is not particularly limited, but the total concentration of the other substances is preferably from 0.0001% by mass to 10% by mass, more preferably from 0.0005% by mass to 1% by mass, and even more preferably from 0.001% by mass to 0.1% by mass, relative to the monomer (excluding the internal crosslinking agent).

[0097] The above-mentioned substance and chelating agent may be added not only to the aqueous monomer solution but also during the polymerization, or these forms may be used in combination.

[0098] The dissolved oxygen in the aqueous monomer solution may be reduced by raising the temperature or by replacing the oxygen with an inert gas.

[0099] The concentration of the monomer in the aqueous monomer solution is selected depending on the selected monomer, decomposition product, and organic solvent. In terms of production efficiency, the lower limit is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The upper limit is preferably 100% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less.

[0100] As long as the object of the present invention is not hindered, additives such as surfactants, density regulators, thickeners, etc. can be added to the aqueous monomer solution. The type and amount of the additives can be appropriately selected depending on the combination of the monomers and organic solvents used.

[0101] [2-2-2] Polymerization process In this step, the aqueous monomer solution described above is polymerized to obtain a hydrous gel-like crosslinked polymer (hereinafter also simply referred to as "hydrous gel").

[0102] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, and reversed phase suspension polymerization, more preferably, aqueous solution polymerization, and reversed phase suspension polymerization, and further preferably, aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable, and either continuous belt polymerization or continuous kneader polymerization is applicable.

[0103] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.

[0104] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization". "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination. For example, the polymerization temperature is preferably 20°C or higher and 100°C or lower, more preferably 40°C or higher and 90°C or lower.

[0105] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen; less than 1 mg / l).

[0106] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the inert gases or the like) are dispersed in an aqueous monomer solution to carry out the polymerization.

[0107] A hydrogel-like crosslinked polymer (hydrogel) is obtained through the polymerization process. The solid content of the hydrogel (solid content concentration, hereinafter, gel solid content) is preferably 25% by mass or more, more preferably 25% by mass or more and 75% by mass or less, even more preferably 25% by mass or more and 65% by mass or less, even more preferably 25% by mass or more and less than 60% by mass, and particularly preferably 40% by mass or more and less than 60% by mass. There is no particular limit on the means for achieving these concentrations, but for example, the above-mentioned "high-temperature initiation polymerization" and / or "high-concentration polymerization" are preferably used. By having the gel solid content (mass%) be equal to or more than the lower limit, the adhesion of the gel is suppressed, and by having the gel solid content be equal to or more than the lower limit, gel crushing, which is performed as necessary, can be efficiently performed.

[0108] The solid content (mass%) of the hydrous gel can be measured by the following measurement method.

[0109] Method for measuring the solid content of hydrous gel (gel solid content) After 2.00 g of the water-absorbent resin (water-containing gel) was placed in an aluminum cup with a bottom diameter of 50 mm, the total mass W5 (g) of the sample (water-containing gel and aluminum cup) was accurately weighed. Next, the sample was placed in an oven with an atmospheric temperature set to 180°C. After 24 hours, the sample was removed from the oven and the total mass W6 (g) was accurately weighed. When the mass of the water-absorbent resin (water-containing gel) used in this measurement was M (g), the water content (100-α) (mass%) of the water-absorbent resin (water-containing gel) was calculated according to the following formula (5). Here, α is the solid content (mass%) of the water-absorbent resin (water-containing gel).

[0110] Formula (5) (100-α)(mass%)={(W5-W6) / M}×100.

[0111] In the present embodiment, the hydrogel obtained through the polymerization step is mixed with a decomposition product of a water-absorbent resin and a crosslinking agent. Hereinafter, the crosslinking agent mixed with the hydrogel is also referred to as an external crosslinking agent.

[0112] The specific means of mixing is not particularly limited, but for example, mixing in the hydrogel crushing step described below can be mentioned. In addition, when a particulate hydrogel in a particle state is directly obtained during the polymerization process, such as gas phase polymerization or reverse phase suspension polymerization, the polymerization step and the gel crushing step are carried out simultaneously or sequentially. In such a polymerization form, the particulate hydrogel obtained by polymerization may be mixed with the water absorbent resin decomposition product and the crosslinking agent, and such a form is also considered to be mixed in the gel crushing step.

[0113] [2-2-3] Hydrogel crushing process (gel crushing process) This step is a step of obtaining a particulate hydrogel (hereinafter also referred to as "particulate hydrogel") by pulverizing the hydrogel obtained in the polymerization step with, for example, a screw extruder such as a kneader or a meat chopper, or a gel pulverizer such as a cutter mill. This step may be carried out two or more times to obtain a particulate hydrogel having a predetermined particle size.

[0114] In addition, when the polymerization step is kneader polymerization, the polymerization step and the gel crushing step are carried out simultaneously. In kneader polymerization, it is preferable to add the decomposition product and the external crosslinking agent when a hydrogel-like crosslinked polymer is formed (when the formation of a hydrogel-like crosslinked polymer is confirmed). Therefore, in kneader polymerization, it is preferable to add the decomposition product and the external crosslinking agent separately after the polymerization reaction of the monomer aqueous solution starts. For example, the decomposition product and the external crosslinking agent are added when a hydrogel-like crosslinked polymer with a polymerization rate of 90% by mass or more is formed.

[0115] If necessary, after the polymerization step and before the gel crushing step, a chopping step may be carried out in which the hydrogel crosslinked polymer is cut or roughly crushed into a size that can be put into a gel crusher using a roller cutter, a guillotine cutter, etc. In particular, when the polymerization step is belt polymerization and a sheet-like or block-like hydrogel is obtained, it is preferable to carry out the chopping step.

[0116] As for the gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.

[0117] In this embodiment, the hydrogel, the water-absorbent resin decomposition product, and the crosslinking agent are mixed in this gel crushing step. The mixing may be a form in which the hydrogel, the water-absorbent resin decomposition product, and the crosslinking agent are mixed in the gel crushing step. The mixing of the hydrogel, the water-absorbent resin decomposition product, and the crosslinking agent in the gel crushing step is not limited to a form in which the hydrogel, the water-absorbent resin decomposition product, and the crosslinking agent are added (all at once or sequentially) to the gel crushing device and mixed. For example, the hydrogel after the polymerization step may be added to the gel crushing device in a state in which the water-absorbent resin decomposition product and the crosslinking agent are added to the hydrogel before the hydrogel is fed into the gel crushing device, and the water-absorbent resin decomposition product and the crosslinking agent are mixed into the hydrogel at the same time as the gel is crushed. In addition, the water-absorbent resin decomposition product and the crosslinking agent may be added to the hydrogel before the shredding step before the gel crushing step, and such a form is also included in the mixing in the gel crushing step. That is, the mixing of the water-absorbent resin decomposition product and the crosslinking agent in the gel crushing step may be in any form as long as the water-containing gel is crushed (disintegrated) in a state in which the water-containing gel, the water-absorbent resin decomposition product, and the crosslinking agent coexist. Also, it may be a combination of the above-mentioned forms. When the addition is performed in the gel crushing step, it is preferable to add the water-absorbent resin decomposition product and the crosslinking agent to the water-containing gel before the gel crushing step and / or during the gel crushing step, and to mix them thoroughly during the gel crushing step. Also, the addition of the water-absorbent resin decomposition product and the crosslinking agent to the water-containing gel may be performed separately or simultaneously. Also, the order of addition of the water-containing gel, the water-absorbent resin decomposition product, and the crosslinking agent is not particularly limited, and may be in any form, such as adding the water-containing gel, the water-absorbent resin decomposition product, and the crosslinking agent simultaneously (to the gel crushing device); adding the water-absorbent resin decomposition product and the crosslinking agent sequentially to the water-containing gel (put into the gel crushing device); adding a mixture of the water-absorbent resin decomposition product and the crosslinking agent to the water-containing gel (put into the gel crushing device).

[0118] The amount of the water-absorbent resin decomposition product added is appropriately set in consideration of production efficiency and the physical properties of the obtained water-absorbent resin, and the water-absorbent resin decomposition product (solid content equivalent) is preferably used in an amount of 1% by mass to 60% by mass, more preferably 3% by mass to 50% by mass, and even more preferably 5% by mass to 40% by mass, based on the total water-absorbent resin (including the decomposition product) (solid content equivalent). By being above the lower limit, the productivity of recycling the water-absorbent resin decomposition product is improved, and by being below the upper limit, the decrease in physical properties due to the addition of the water-absorbent resin decomposition product can be suppressed.

[0119] The solid content concentration of the water-absorbent resin decomposition product when mixed with the hydrous gel is preferably 1% by mass or more, more preferably 5% by mass or more and 100% by mass or less, and even more preferably 5% by mass or more and 99% by mass or less. By being equal to or more than the lower limit, the productivity when recycling the water-absorbent resin decomposition product is improved.

[0120] When mixing the hydrogel-like crosslinked polymer and the water-absorbent resin decomposition product, it is preferable that the solid content concentration of the water-absorbent resin decomposition product is ≧ the solid content concentration of the hydrogel-like crosslinked polymer. By making the solid content concentration of the water-absorbent resin decomposition product ≧ the solid content concentration of the hydrogel-like crosslinked polymer, even when the recovered water-absorbent resin is used as a raw material, a water-absorbent resin having improved water absorption performance (particularly water absorption capacity under pressure) can be obtained. When the solid content concentration of the water-absorbent resin decomposition product ≧ the solid content concentration of the hydrogel-like crosslinked polymer, it is considered that the crosslinking between the water-absorbent resin decomposition product and the crosslinked polymer is prioritized over the crosslinking within the hydrogel-like crosslinked polymer, and the crosslinking between the two is likely to proceed. In a preferred embodiment, the solid content concentration of the water-absorbent resin decomposition product is 10% by mass or more higher than the solid content concentration of the hydrous gel (solid content concentration of the water-absorbent resin decomposition product-solid content concentration of the hydrous gel-like crosslinked polymer≧10% by mass), may be 20% by mass or more and 60% by mass or less higher (20% by mass≦(solid content concentration of the water-absorbent resin decomposition product-solid content concentration of the hydrous gel-like crosslinked polymer)≦60% by mass), or may be 30% by mass or more and 50% by mass or less higher (30% by mass≦(solid content concentration of the water-absorbent resin decomposition product-solid content concentration of the hydrous gel-like crosslinked polymer)≦50% by mass). Another preferred embodiment is such that the solid content concentration of the hydrogel is 25% by mass or more and 75% by mass or less, and the solid content concentration of the decomposition product of the water-absorbent resin is 20% by mass or more and 60% by mass or less higher than the solid content concentration of the hydrogel-like crosslinked polymer; or such that the solid content concentration of the hydrogel is 40% by mass or more and 60% by mass or less, and the solid content concentration of the decomposition product of the water-absorbent resin is 30% by mass or more and 50% by mass or less higher than the solid content concentration of the hydrogel-like crosslinked polymer.

[0121] To achieve the above-mentioned preferred embodiment, the solid content of the hydrogel and / or the solid content of the decomposition product of the water-absorbent resin may be adjusted by adding water, drying, or the like.

[0122] The crosslinking agent (external crosslinking agent) added together with the decomposition product of the water-absorbent resin may have a total of two or more polymerizable unsaturated groups and / or reactive functional groups in one molecule. Preferably, the external crosslinking agent is a crosslinking agent having a reactive functional group in the molecule that can react with a functional group (e.g., a carboxyl group) in the decomposition product of the water-absorbent resin and a functional group (e.g., a carboxyl group) in the hydrogel.

[0123] Specific examples of the external crosslinking agent include polyhydric alcohol compounds, epoxy compounds, polyamine compounds or condensates thereof with haloepoxy compounds, oxazoline compounds, (mono-, di-, or poly)oxazolidinone compounds, alkylene carbonate compounds, and polyfunctional acrylate compounds.

[0124] Examples of crosslinking agents having a plurality of polymerizable unsaturated groups (copolymerizable with monomers) in the molecule include N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin (meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, trimethylolpropane di(meth)allyl ether, poly(meth)allyl ether of polyol having 2 to 10 carbon atoms, pentaerythritol triallyl ether, and tetraallyloxyethane. When using a crosslinking agent having a plurality of polymerizable unsaturated groups (copolymerizable with monomers) in the molecule, it is preferable to use a radical generator in combination. Examples of such radical generators include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. A reducing agent may be used in combination with the radical generator. Examples of the reducing agent include those listed in the section on decomposers of the water-absorbent resin decomposition product. The amount of the radical generator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.005 mol% or more and 0.5 mol% or less, based on the monomers (excluding the internal crosslinking agent) constituting the hydrogel.

[0125] Examples of external crosslinking agents having multiple reactive functional groups (which can react with functional groups of monomers (e.g., carboxy groups)) in the molecule include triallylamine, polyallyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerin, 1,4-butanediol, pentaerythritol, ethylenediamine, ethylene carbonate, propylene carbonate, polyethyleneimine, etc. Examples of external crosslinking agents having polymerizable unsaturated groups and reactive functional groups in the molecule include glycidyl (meth)acrylate, etc.

[0126] Among them, since the decomposition product of the water absorbent resin is easily and efficiently incorporated into the crosslinked polymer, the external crosslinking agent preferably contains at least one selected from the group consisting of an epoxy compound, a polyhydric alcohol compound, and an alkylene carbonate compound, more preferably an epoxy compound, even more preferably (poly)ethylene glycol diglycidyl ether, and particularly preferably ethylene glycol diglycidyl ether.

[0127] The amount of the external crosslinking agent added is appropriately set according to the type of monomer and external crosslinking agent constituting the water-absorbent resin. The amount of the external crosslinking agent added is preferably 0.005 mol% or more and 5 mol% or less, more preferably 0.01 mol% or more and 2 mol% or less, and even more preferably 0.01 mol% or more and 1 mol% or less, relative to the monomer (excluding the internal crosslinking agent) constituting the hydrogel-like crosslinked polymer. By being equal to or more than the lower limit, the decomposition product of the water-absorbent resin is easily incorporated into the crosslinked polymer efficiently, and by being equal to or less than the upper limit, the decrease in the water-absorbent resin's water-absorbency performance (for example, water-absorbency ratio) is suppressed.

[0128] The external crosslinking agent is preferably added as an aqueous solution. In this case, the concentration of the external crosslinking agent can be, for example, 0.1% by mass or more and 5% by mass or less. If necessary, a hydrophilic organic solvent may be used, and the amount of the organic solvent used in the aqueous solution is preferably 10% by mass or less, more preferably 5% by mass or less.

[0129] When mixing the crosslinking agent (aqueous solution) with the hydrogel, an acid catalyst, a basic catalyst, water-insoluble fine particles, or a surfactant may be present in a range that does not impair the effects of the present invention, for example, 0 to 10 parts by mass, preferably 0 to 5 parts by mass, and more preferably 0 to 1 part by mass. The surfactants to be used and the amounts thereof are exemplified in U.S. Pat. No. 7,473,739 and the like.

[0130] In the production method according to the present invention, a thickener may be added before and / or during the gel crushing step, which improves the kneading properties in the gel crushing device.

[0131] Specific examples of the thickener include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified ethylene-propylene-diene terpolymer (EPDM), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, polyalkylene oxide such as ethyl cellulose, ethylhydroxyethyl cellulose, and polyethylene glycol, and polysiloxane modified with side chain and / or terminal polyether. The molecular weight (mass average molecular weight) of these is preferably selected appropriately within the range of 200 to 2,000,000, more preferably 400 to 1,000,000. Two or more of these may be used in combination.

[0132] The amount of the thickener added is preferably 5% by mass or less, more preferably 3% by mass or less, and is preferably 0.001% by mass or more, particularly preferably 0.01% by mass or more, based on the solid content of the hydrogel.

[0133] The temperature of the hydrogel when mixed with the decomposition product and the crosslinking agent may be 25°C or higher, preferably 50°C or higher, more preferably 50°C or higher and 200°C or lower, even more preferably 55°C or higher and 180°C or lower, and particularly preferably 55°C or higher and 100°C or lower. When the temperature of the hydrogel when mixed is above the lower limit, the crosslinking reaction with the decomposition product is easily promoted, and as a result, the water absorption performance (particularly the water absorption capacity under pressure) can be improved, which is preferable. In addition, when the temperature of the hydrogel when mixed is below the upper limit, the drying of the hydrogel can be suppressed.

[0134] The temperature of the water-absorbent resin decomposition product when mixed with the hydrogel and the crosslinking agent may be 25°C or higher, preferably 50°C or higher, more preferably 50°C or higher and 200°C or lower, even more preferably 55°C or higher and 180°C or lower, and particularly preferably 55°C or higher and 100°C or lower. When the temperature of the water-absorbent resin decomposition product when mixed is above the lower limit, the crosslinking reaction with the hydrogel is easily promoted, and as a result, the water absorption performance (particularly the water absorption capacity under pressure) can be improved, which is preferable. When the temperature of the water-absorbent resin decomposition product when mixed is below the upper limit, the drying of the water-absorbent resin decomposition product can be suppressed.

[0135] The temperature of the hydrogel or the decomposition product of the water-containing gel or the water-absorbent resin during mixing can be adjusted by adjusting the temperature of the hydrogel or the decomposition product of the water-absorbent resin to a predetermined temperature in advance before feeding into the gel crusher, and by keeping the temperature in the gel crusher using a heat-retaining means such as a jacket.

[0136] [2-2-4] Drying process This step is a step of obtaining a dry polymer by drying the particulate hydrogel obtained in the polymerization step and / or pulverization step to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.

[0137] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.

[0138] The drying temperature (hot air temperature) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of the color tone of the water-absorbent resin, drying efficiency, etc. In addition, the drying conditions other than the drying temperature, such as the wind speed of the hot air and the drying time, may be appropriately set according to the water content and total mass of the particulate hydrogel to be dried and the target resin solid content. When band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.

[0139] By setting the above-mentioned drying temperature, drying time, etc. within the above-mentioned ranges, the desired properties (e.g., CRC, water absorption capacity under pressure, water-soluble content, and color tone, particularly water-soluble content) of the obtained water absorbent resin can be set within a desired range.

[0140] By the above operation, the decomposition product of the water absorbent resin is incorporated inside the crosslinked polymer. Hereinafter, the product "in which the decomposition product of the water absorbent resin is incorporated inside the crosslinked polymer" is also referred to as "incorporated water absorbent resin". Next, it is preferable to carry out a surface crosslinking step on this incorporated water absorbent resin. This can improve the water absorption characteristics (particularly the water absorption capacity under pressure). In addition, the water absorbent resin obtained by the drying step is also referred to as a water absorbent resin precursor.

[0141] [2-2-5] Surface crosslinking process This step is a step of providing a portion with a higher crosslink density on a surface layer (particularly, a portion several tens of μm from the surface of the water absorbent resin precursor) of the incorporated water absorbent resin obtained through the above-mentioned steps, and can be composed of a mixing step, a heat treatment step, and a cooling step (optional).

[0142] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the incorporated water-absorbent resin.

[0143] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but includes organic or inorganic surface cross-linking agents. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., organic surface cross-linking agents that react with carboxyl groups are preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 can be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal compounds, alkylene carbonate compounds, cyclic urea compounds, etc. can be mentioned.

[0144] Specifically, polyhydric alcohol compounds such as ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerin, polyglycerin, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,2-cyclohexanol, trimethylolpropane, diethanolamine, triethanolamine, polyoxypropylene, oxyethylene-oxypropylene block copolymer, pentaerythritol, and sorbitol; ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol Epoxy compounds such as cerol polyglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol polyglycidyl ether, glycidol, sorbitol polyglycidyl ether, pentaerythritol polyglycidyl ether, trimethylolpropane polyglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether; polyamine compounds and inorganic or organic salts thereof such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, and polyethyleneimine; polyisocyanate compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; aziridine compounds such as polyaziridine; polyoxazoline compounds such as 1,2-ethylenebisoxazoline, bisoxazoline, and polyoxazoline; carbonic acid derivatives such as urea, thiourea, guanidine, dicyandiamide, and 2-oxazolidinone;1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, 1,3-dioxopane alkylene carbonate compounds such as dimethyl-2-one; haloepoxy compounds such as epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, and polyvalent amine adducts thereof; oxetane compounds; silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane; polyvalent metal compounds such as hydroxides, chlorides, sulfates, nitrates, or carbonates of zinc, calcium, magnesium, aluminum, iron, zirconium, and the like; and the like. Among these, two or more may be used in combination. Among the above surface crosslinking agents, one or more selected from polyvalent metal compounds, epoxy compounds, oxazoline compounds, and alkylene carbonate compounds are preferred.;

[0145] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.5 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin precursor.

[0146] In addition, each of the additives described below can be added by mixing it with the surface cross-linking agent (aqueous solution) in an amount of 5 parts by mass or less, or can be added separately in this mixing step.

[0147] (Mixing process) This step is a step of mixing the water-absorbent resin precursor with the surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the liquid with the water-absorbent resin precursor is preferred. In this case, the surface crosslinking agent solution is mixed with the water-absorbent resin precursor by more preferably spraying or dropping, and more preferably spraying.

[0148] The device for carrying out the mixing is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.

[0149] (Heat treatment process) This step is a step in which heat is applied to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin precursor.

[0150] The device for carrying out the crosslinking reaction is not particularly limited, but preferably includes a paddle dryer. The reaction temperature in the crosslinking reaction is appropriately set according to the type of surface crosslinking agent used, and is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less. The reaction time in the crosslinking reaction is appropriately set according to the water content of the object of the heat treatment process, the type of surface crosslinking agent, the thermal efficiency of the heating device, etc., and it is preferable to heat until the water content becomes 10% by mass or less. For example, the reaction time in the crosslinking reaction is, for example, 10 minutes or more and 120 minutes or less, and preferably 30 minutes or more and 90 minutes or less.

[0151] (cooling process) This step is an optional step that is installed as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The surface-crosslinked water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, in the cooling step, preferably to 40°C or more and 80°C or less, more preferably to 50°C or more and 70°C or less.

[0152] After the surface cross-linking step, a sizing step may be further carried out. In addition to the above, the method according to the present invention may include at least one step selected from the steps of adding various additives, removing fine powder, recycling fine powder (recovering fine powder), and filling. Furthermore, various known steps may be included depending on the purpose. The fine powder removed in the removing fine powder step may be used as a recovered water absorbent resin.

[0153] [2-2-6] Particle sizing process This step is a step for adjusting the particle size of the surface-crosslinked water-absorbent resin precursor. This particle size adjustment step provides a water-absorbent resin whose particle size or particle size distribution is more actively controlled.

[0154] Preferably, the sizing step includes a crushing step and / or a classification step. The crushing step is a step of adjusting the particle size by crushing the loosely aggregated granular material after the surface cross-linking step with a crusher. The classification step is a step of removing coarse particles and fine powder from the surface cross-linked granular material or the crushed material thereof with a classifier.

[0155] The crusher is not particularly limited, and examples thereof include a vibration mill, a roll granulator, a knuckle type crusher, a roll mill, a high-speed rotary crusher (pin mill, hammer mill, screw mill), a cylindrical mixer, etc. Those that cause little damage to the dried material or the surface-crosslinked dried material are preferred, and specific examples thereof include a roll granulator (Matsubo Corporation), a granulator (Kurimoto Iron Works, Ltd.), and a Randel Mill (Tokuju Corporation). As a classifier, a vibrating or rocking sieve classifier using a sieve net is used.

[0156] [2-2-7] Fine powder recycling process The "fine powder recycling process" means a process in which the fine powder removed in the classification step is supplied to any process as it is or after granulating the fine powder. Preferably, it is a process in which the fine powder or the fine powder granules are fed to a process before the drying process to reuse them. Examples of processes before the drying process include a monomer aqueous solution preparation process, a polymerization process, a pulverization process of the hydrogel after polymerization, and a drying process of the granular hydrogel. The fine powder may be added to these processes as it is, or may be added after swelling and gelling with water or granulating. In addition, water, a crosslinking agent, a binder other than water (e.g., a water-soluble polymer, a thermoplastic resin), a polymerization initiator, a reducing agent, a chelating agent, a coloring inhibitor, etc. may be added together with the fine powder. The preferred amount of fine powder recovery is appropriately set depending on the target particle size.

[0157] [2-2-8] Other processes In addition to the steps described above, the production method according to the present invention may further include a grinding step, a classification step, a rewetting step, a granulation step, a transportation step, a storage step, a packaging step, a keeping step, and the like, as necessary.

[0158] (Other additives) Other than the optionally used surface crosslinking agent, conventionally known components such as polymer powder (e.g., starch such as tapioca starch acetate), inorganic fine particles, dust inhibitor, dried water absorbent resin (fine powder), liquid permeability improver, reducing agent (e.g., sodium sulfite), and antioxidant can be further added as other additives before or after drying.

[0159] [3] Physical properties of water-absorbent resins as products With regard to the water absorbent resin obtained by the production method according to the present invention (particularly, a water absorbent resin obtained by subjecting an incorporated water absorbent resin to a surface cross-linking treatment), when the water absorbent resin is used in an absorbent article, particularly, a disposable diaper, it is desirable that at least one of the following [3-1] and [3-2] is satisfied.

[0160] [3-1] AAP0.3 (water absorption rate under pressure) The water-absorbent resin produced by the method according to the present invention can improve AAP0.3 (absorption capacity under pressure). The AAP0.3 (absorption capacity under pressure) of the water-absorbent resin produced by the method according to the present invention may be 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, 25 g / g or more, 25.5 g / g or more, 26 g / g or more, or 27 g / g or more. By setting AAP0.3 (absorption capacity under pressure) to such a lower limit, the amount of liquid returning when pressure is applied to the absorbent body (sometimes referred to as "Re-Wet") can be kept low, and the water-absorbent resin becomes suitable for absorbent body applications of absorbent articles such as disposable diapers and sanitary napkins. In one embodiment, the AAP0.3 (absorption capacity under pressure) of the water-absorbent resin is 40 g / g or less, 35 g / g or less, or 30 g / g or less. The AAP0.3 (water absorption capacity against pressure) can be controlled by a known technique, for example, by the crosslinking density of the surface crosslinked layer.

[0161] [3-2] CRC (absorption capacity without pressure) The absorbency under no load (CRC) of the water-absorbent resin produced by the method according to the present invention is usually 5 g / g or more, and may be 15 g / g or more, 25 g / g or more, 28 g / g or more, or 30 g / g or more. There is no particular limit to the upper limit, and a higher CRC is preferable, but from the viewpoint of balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less. If the CRC is less than 5 g / g, the absorption amount is small and it is not suitable for use as an absorbent for absorbent articles such as disposable diapers. Also, if the CRC is more than 70 g / g, the speed of absorbing body fluids such as urine and blood decreases, and it is not suitable for use in disposable diapers with high water absorption speed.

[0162] [3-3] AAP0.3 reduction rate The water absorbent resin produced by the method according to the present invention has a smaller AAP0.3 (absorption capacity under pressure) than a water absorbent resin (reference water absorbent resin) produced in the same manner except that no decomposition product is used. In one embodiment, the AAP0.3 reduction rate of the water absorbent resin produced by the method according to the present invention is 10% or less. In one embodiment, the AAP0.3 reduction rate of the water absorbent resin is preferably 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, or 4% or less.

[0163] In this specification, the AAP0.3 reduction rate is the reduction rate of the AAP0.3 (absorption capacity under pressure) of the water absorbent resin relative to the AAP0.3 (absorption capacity under pressure) of the water absorbent resin (reference water absorbent resin) produced in the same manner except that the decomposition product is not used. Specifically, the AAP0.3 reduction rate is a value obtained by determining the AAP0.3 (absorption capacity under pressure) of the water absorbent resin and the reference water absorbent resin, calculating to the second decimal place according to the following formula: AAP0.3 reduction rate = [(AAP0.3 (g / g) of the reference water absorbent resin) - (AAP0.3 (g / g) of the water absorbent resin)] × 100 / (AAP0.3 (g / g) of the reference water absorbent resin), and rounding it off to the first decimal place.

[0164] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.

[0165] The present invention encompasses the following aspects and configurations.

[0166] 1. The method comprises producing a water absorbent resin by using a decomposed product of the water absorbent resin obtained by decomposing the recovered water absorbent resin as a part of a raw material, A method for producing a water-absorbent resin, comprising mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, a decomposition product of the water-absorbent resin, and a crosslinking agent.

[0167] 2. The method for producing a water-absorbing resin according to 1 above, wherein the crosslinking agent has a reactive functional group in the molecule.

[0168] 3. The method for producing a water-absorbent resin according to 1 or 2 above, wherein the temperature of the hydrogel cross-linked polymer during the mixing is 50° C. or higher.

[0169] 4. The method for producing a water-absorbent resin according to any one of 1. to 3., wherein, when mixing the hydrogel-like crosslinked polymer and the decomposition product of the water-absorbent resin, a solid content concentration of the decomposition product of the water-absorbent resin is equal to or greater than a solid content concentration of the hydrogel-like crosslinked polymer.

[0170] 5. The method for producing a water-absorbent resin according to any one of 1. to 4., wherein the decomposition product of the water-absorbent resin is used in an amount of 1% by mass or more and 60% by mass or less based on the total amount of the water-absorbent resin.

[0171] 6. The method for producing a water-absorbent resin according to any one of 1. to 5., wherein the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article. EXAMPLES

[0172] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. In the following examples, unless otherwise specified, operations were performed at room temperature (25°C). Furthermore, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.

[0173] [Manufacturing example a] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 103.7 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 314.3 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (a').

[0174] Next, the monomer aqueous solution (a') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (a). At this time, the temperature of the monomer aqueous solution (a) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0175] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (a), and the mixture was immediately poured into a stainless steel vat-shaped container in an open-air system. The time from the start of the second neutralization to the pouring of the aqueous solution of monomer (a) into the vat-shaped container was 55 seconds, and the vat-shaped container was heated using a hot plate until the surface temperature reached 40°C.

[0176] The polymerization reaction started 60 seconds after the aqueous monomer solution (a) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. Three minutes after the start of the polymerization reaction, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") (S1) was taken out. The series of operations were carried out in an open-to-air system.

[0177] The hydrogel (S1) obtained by the polymerization reaction was cut into strips and crushed using a meat chopper with a die diameter of 7.5 mm. The hydrogel (S1) was then spread on a 50-mesh wire net and dried with hot air at 190°C for 60 minutes.

[0178] Next, the mixture was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water-absorbent resin precursor (S1) in an irregularly pulverized state.

[0179] 100 parts by mass of the obtained water absorbent resin precursor (S1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was heated at 100° C. for 45 minutes.

[0180] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (S1). The water-absorbent resin (S1) had a CRC of 37.7 g / g and an AAP0.3 of 28.4 g / g.

[0181] [Production Example 1] Into a reaction vessel equipped with an agitator, 100 parts by mass of the water absorbent resin (S1) obtained in Production Example a, 733 parts by mass of deionized water, 149.3 parts by mass of a 15% by mass aqueous solution of sodium carbonate as a pH adjuster, and 6.67 parts by mass of 30% by mass hydrogen peroxide as a decomposition agent were added, and mixed with a stirrer to obtain a mixture (A).

[0182] Next, the decomposition reaction was initiated by immersing the reaction vessel containing the mixture (A) in a thermostatic bath at 80° C. After 60 minutes had passed, it was confirmed that the gel-like matter had been completely solubilized.

[0183] Next, in order to remove hydrogen peroxide remaining in the system, 80.7 parts by mass of 15% by mass sodium carbonate was added and stirring was continued for 1 hour. After 1 hour, the liquid temperature in the reaction vessel was cooled to room temperature to obtain decomposition product (1) (aqueous solution). The decomposition product (1) had a solid content concentration of 9.37% by mass and a mass average molecular weight Mw of 483,000.

[0184] [Production Example 2] To 100 parts by mass of the water absorbent resin (S1) obtained in Production Example a, 5.83 parts by mass of 30% hydrogen peroxide as a decomposition agent and 2.0 parts by mass of deionized water were added, and the mixture composition was mixed in a Loedige mixer to obtain a mixture (B).

[0185] The obtained mixture (B) was placed in a reaction vessel equipped with a stirrer heated in an oil bath at 190°C, and heat-treated for 30 minutes with stirring while controlling the atmosphere in the space of the vessel to a dew point of 90°C and a temperature of 190°C, thereby obtaining a decomposition product (2) (powder form).

[0186] The obtained decomposition product (2) had a decomposition rate of 97.0%, a solid content concentration of 93.6% by mass, and a mass average molecular weight Mw of 305,000.

[0187] [Example 1] A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and mixed to prepare an aqueous monomer solution (1').

[0188] Next, the monomer aqueous solution (1') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (1). At this time, the temperature of the monomer aqueous solution (1) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.

[0189] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (1), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the aqueous monomer solution (1) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0190] The polymerization reaction started 60 seconds after the aqueous monomer solution (1) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (1) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-to-air system.

[0191] The hydrous gel (1) obtained by the polymerization reaction was cut into strips (solid concentration: 46.1% by mass) (585.7 g) and the decomposition product (1) obtained in Production Example 1 (320.2 g, solid concentration: 9.37% by mass) were both adjusted to 30°C, and then the hydrous gel (1), the decomposition product (1), and 30.3 g of a 0.89% by mass aqueous solution of ethylene glycol diglycidyl ether (0.050 mol% relative to the carboxyl group-containing unsaturated monomer) as an external crosslinking agent were continuously fed into a meat chopper having a die diameter of 7.5 mm to crush the gel, thereby obtaining a crushed gel product (1).

[0192] The obtained gel pulverized material (1) was spread on a 50-mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (1).

[0193] A surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (1), and the mixture was subjected to a heat treatment at 100°C for 45 minutes.

[0194] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (1). The obtained recycled water absorbent resin (1) had a CRC of 37.5 g / g and an AAP0.3 of 26.7 g / g.

[0195] [Example 2] A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and mixed to prepare an aqueous monomer solution (2').

[0196] Next, the monomer aqueous solution (2') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (2). At this time, the temperature of the monomer aqueous solution (2) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.

[0197] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (2), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the aqueous monomer solution (2) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0198] The polymerization reaction started 60 seconds after the aqueous monomer solution (2) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-to-air system.

[0199] The hydrous gel (2) obtained by the polymerization reaction was cut into strips (solid concentration: 46.1% by mass) (585.7 g) and the decomposition product (1) obtained in Production Example 1 (320.2 g, solid concentration: 9.37% by mass) were both adjusted to 60°C, and then the hydrous gel (2), the decomposition product (1) and 30.3 g of a 0.89% by mass aqueous solution of ethylene glycol diglycidyl ether (0.050 mol% relative to the carboxyl group-containing unsaturated monomer) as an external crosslinking agent were continuously fed into a meat chopper having a die diameter of 7.5 mm to crush the gel, thereby obtaining a crushed gel product (2).

[0200] The obtained gel pulverized material (2) was spread on a 50-mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (2).

[0201] 100 parts by mass of the obtained water absorbent resin precursor (2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.

[0202] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (2). The obtained recycled water absorbent resin (2) had a CRC of 37.6 g / g and an AAP0.3 of 26.9 g / g.

[0203] [Example 3] A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and mixed to prepare an aqueous monomer solution (3').

[0204] Next, the monomer aqueous solution (3') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (3). At this time, the temperature of the monomer aqueous solution (3) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.

[0205] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (3), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the aqueous monomer solution (3) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0206] The polymerization reaction started 60 seconds after the aqueous monomer solution (3) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (3) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-to-air system.

[0207] The hydrous gel (3) obtained by the polymerization reaction was cut into strips (solid concentration: 46.1% by mass), and 585.7 g of the decomposition product (2) obtained in Production Example 2 (solid concentration: 93.6% by mass) were both adjusted to 30°C. Then, the hydrous gel (3), the decomposition product (2), and 30.3 g of a 0.89% by mass aqueous solution of ethylene glycol diglycidyl ether (0.050 mol% relative to the carboxyl group-containing unsaturated monomer) as an external crosslinking agent were continuously fed into a meat chopper having a die diameter of 7.5 mm to crush the gel, thereby obtaining a crushed gel product (3).

[0208] The obtained gel pulverized material (3) was spread on a 50-mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (3).

[0209] 100 parts by mass of the obtained water absorbent resin precursor (3) was uniformly mixed with a surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.

[0210] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (3). The obtained recycled water absorbent resin (3) had a CRC of 37.6 g / g and an AAP0.3 of 27.3 g / g.

[0211] [Example 4] A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and mixed to prepare an aqueous monomer solution (4').

[0212] Next, the monomer aqueous solution (4') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (4). At this time, the temperature of the monomer aqueous solution (4) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to form a transparent homogeneous solution.

[0213] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (4), and the mixture was immediately poured into a stainless steel vat-type container in an open-to-air system. The time from the start of the second neutralization stage to pouring the aqueous monomer solution (4) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0214] The polymerization reaction started 60 seconds after the aqueous monomer solution (4) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. Three minutes after the start of the polymerization reaction, the hydrogel (4) was taken out. The series of operations was carried out in an open-to-air system.

[0215] The hydrous gel (4) obtained by the polymerization reaction was cut into strips (solid concentration: 46.1% by mass), and 585.7 g of the decomposition product (2) obtained in Production Example 2 (solid concentration: 93.6% by mass) were both adjusted to 60°C. Then, the hydrous gel (4), the decomposition product (2), and 30.3 g of a 0.89% by mass aqueous solution of ethylene glycol diglycidyl ether (0.050 mol% relative to the carboxyl group-containing unsaturated monomer) as an external crosslinking agent were continuously fed into a meat chopper having a die diameter of 7.5 mm to crush the gel, thereby obtaining a crushed gel product (4).

[0216] The obtained gel pulverized material (4) was spread on a 50-mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (4).

[0217] 100 parts by mass of the obtained water absorbent resin precursor (4) was uniformly mixed with a surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.

[0218] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (4). The obtained recycled water absorbent resin (4) had a CRC of 37.9 g / g and an AAP0.3 of 27.6 g / g.

[0219] [Comparative Example 1] A reaction vessel was charged with 220.4 g of acrylic acid, 0.56 g (0.035 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (C1').

[0220] Next, the monomer aqueous solution (C1') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (C1). At this time, the temperature of the monomer aqueous solution (C1) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0221] Next, 10.9 g of 4.0 mass % aqueous sodium persulfate solution was added to the stirred aqueous monomer solution (C1), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to pouring the aqueous monomer solution (C1) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0222] The polymerization reaction started 60 seconds after the monomer aqueous solution (C1) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (C1) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.

[0223] The hydrous gel (C1) obtained by the polymerization reaction was cut into strips (585.7 g, solid content concentration 46.1% by mass) and the decomposition product (1) obtained in Production Example 1 (320.2 g, solid content concentration 9.37% by mass) were both adjusted to 30°C, and then the gel was crushed by being continuously fed into a meat chopper having a die diameter of 7.5 mm to obtain a crushed gel product (C1).

[0224] The obtained gel pulverized material (C1) was spread on a 50 mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (C1).

[0225] 100 parts by mass of the obtained water absorbent resin precursor (C1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water, and the mixture was subjected to heat treatment at 100°C for 45 minutes.

[0226] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (C1). The obtained recycled water absorbent resin (C1) had a CRC of 37.8 g / g and an AAP0.3 of 25.1 g / g.

[0227] [Comparative Example 2] A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 282.6 g of deionized water, and mixed to prepare an aqueous monomer solution (C2').

[0228] Next, the monomer aqueous solution (C2') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (C2). At this time, the temperature of the monomer aqueous solution (C2) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0229] Next, 10.9 g of 4.0% by mass aqueous sodium persulfate solution was added to the stirred aqueous monomer solution (C2), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to pouring the aqueous monomer solution (C2) into the vat-type container was 55 seconds, and the vat-type container was heated using a hot plate until the surface temperature reached 40°C.

[0230] The polymerization reaction started 60 seconds after the monomer aqueous solution (C2) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (C2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.

[0231] The hydrous gel (C2) obtained by the polymerization reaction was cut into strips (585.7 g, solid content: 46.1% by mass) and 32.1 g of the decomposition product (2) obtained in Production Example 2 (solid content: 93.6% by mass) were both adjusted to 30°C, and then the gel was crushed by continuously feeding them into a meat chopper with a die diameter of 7.5 mm to obtain the crushed gel product (C2).

[0232] The obtained gel pulverized material (C2) was spread on a 50 mesh wire net, dried with hot air at 190°C for 60 minutes, pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (C2).

[0233] A surface crosslinking agent solution consisting of 0.020 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol (PG) and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (C2), and the mixture was subjected to heat treatment at 100°C for 45 minutes.

[0234] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (C2). The obtained recycled water absorbent resin (C2) had a CRC of 37.4 g / g and an AAP0.3 of 25.3 g / g.

[0235] [Table 1]

[0236] (summary) Table 1 shows the water absorption properties of the water absorbent resins produced by adding the decomposition product of the water absorbent resin in the gel crushing step.

[0237] In comparison with the water absorbent resin (S1) produced only from the monomer raw material of Production Example a, the AAP0.3 of the water absorbent resin of Comparative Examples 1 and 2, in which the water absorbent resin decomposition product was used as part of the raw material in the gel crushing process, was reduced by 10% or more.

[0238] On the other hand, in Examples 1 to 4 in which an external crosslinking agent capable of reacting with the decomposition product of the water absorbent resin was added simultaneously in the gel crushing step, the decrease in AAP0.3 of the water absorbent resin was suppressed to 2.8 to 6.0%.

[0239] A comparison between Examples 1 and 2, or between Examples 3 and 4 shows that the AAP0.3 is improved by increasing the material temperature during gel grinding.

[0240] In addition, from a comparison between Examples 1 and 3, or Examples 2 and 4, it can be seen that the AAP0.3 is improved by increasing the solids concentration of the decomposition product of the water-absorbent resin to be added to be higher than the solids concentration of the hydrogel to be pulverized and mixed at the same time.

Claims

1. The method comprises producing a water absorbent resin by using a decomposed product of the water absorbent resin obtained by decomposing the recovered water absorbent resin as a part of a raw material, A method for producing a water-absorbent resin, comprising mixing a hydrous gel-like crosslinked polymer obtained by polymerizing an unsaturated monomer, a decomposition product of the water-absorbent resin, and a crosslinking agent in a gel crushing step.

2. The method for producing a water-absorbing resin according to claim 1, wherein the crosslinking agent has a reactive functional group in the molecule.

3. The method for producing a water-absorbent resin according to claim 1 or 2, wherein the temperature of the hydrogel cross-linked polymer during the mixing is 50° C. or higher.

4. 3. The method for producing a water-absorbent resin according to claim 1, wherein, when mixing the hydrogel-like crosslinked polymer and the water-absorbent resin decomposition product, a solid content concentration of the water-absorbent resin decomposition product is greater than or equal to a solid content concentration of the hydrogel-like crosslinked polymer.

5. The method for producing a water-absorbent resin according to claim 1 or 2, wherein the decomposition product of the water-absorbent resin is used in an amount of 1% by mass or more and 60% by mass or less based on the total amount of the water-absorbent resin.

6. The method for producing a water-absorbent resin according to claim 1 or 2, wherein the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article.

7. The method for producing a water-absorbent resin according to claim 1 or 2, wherein a decomposition rate of the decomposition product of the water-absorbent resin is 75% or more.

Citation Information

Patent Citations

  • Method for producing water-absorbing resin particles

    WO2020213298A1

  • Method for producing water-absorbing resin particles

    WO2022080342A1